Association between self-reported and proxy informant Health Quality of life of older adults with the use of antipsychotic drugs in nursing homes. A cross-sectional study - Denis Boucaud-Maitre; Fares Jaballah; Luc Letenneur; Leila Rinaldo; Jean-François Dartigues; Moustapha Dramé; Hélène Amieva; Maturin Tabué-Teguo (PLoS ONE, 2025)
Introduction Antipsychotic prescriptions are frequent in nursing homes due to the challenging management of symptoms associated with Alzheimer’s disease and related neurodegenerative disorders. This study aimed to assess the association between Health-related Quality Of Life (HrQOL) and antipsychotic use in nursing homes. Methods This is a cross-sectional study of the KASEHPAD (Karukera Study of Ageing in Nursing Homes) study conducted in six nursing homes in Guadeloupe and Martinique (French West Indies). The EuroQol 5-dimensional questionnaire (EQ-5D) was used to measure HRQoL. Clinical characteristics and use of antipsychotic drugs of 194 older adults with both self-reported and proxy informant HrQOL index were extracted. Other outcomes measures included the frequency and severity of delusions, hallucinations and agitation using the reduced Neuropsychiatric Inventory Nursing Home (NPI-R) score, Activities of Daily Living (ADL) score and Mini-Mental State Examination (MMSE) score. Results The mean age of participants was 81.3 years and 63.6% had major cognitive impairment (MMSE score ≤18). The prevalence of delusions (39.7%), hallucinations (27.8%) and agitation (40.7%) was high. Antipsychotic medication was prescribed to 37.1% of the participants. The self-reported HrQOL Index of older adults was higher than the proxy HrQOL Index (0.54 ± 0.43 versus 0.40 ± 0.43) with a correlation coefficient of 0.63 (p<0.001). The use of antipsychotic medication was associated with a higher self-reported HrQOL index, after controlling for the frequency (β = 0.144, p = 0.024) or severity (β = 0.159, p = 0.009) of delusions, hallucinations and agitation symptoms. Conversely, antipsychotic use was not associated with proxy HrQOL Index. Conclusion Despite the adverse effects of long-term use of antipsychotic drugs in older adults, it is associated with better-perceived HrQOL among nursing home residents. However, this association was not observed when HrQOL was assessed by proxy informants. This finding may explain the challenges in reducing the use of this therapeutic class in nursing homes.